Three New Fungal Leaf Spot Diseases of Spinach in the United States and the Evaluation of Fungicide Efficacy for Disease Management - Liu, Bo (Plant disease, 2021)
Leaf spot diseases of spinach, caused by Colletotrichum spinaciae, has become a major production constraint in several production areas, including Texas, in recent years. Leaf spot symptoms were observed in several fields in Texas in 2016 and 2017, with typical anthracnose-like symptoms and leaves with small, circular, and sunken lesions that appeared similar to injury from windblown sand. The lesions were plated on potato dextrose agar, from which fungal cultures were recovered. The fungi were identified based on morphology and sequence analysis of the introns of glutamate synthetase and glyceraldehyde-3-phosphate dehydrogenase (for isolates determined to be Colletotrichum spp.) and the internal transcribed spacer ribosomal DNA (for isolates determined to be Myrothecium spp.). Based on foliar symptoms, fungal colony and spore morphology, pathogenicity tests of fungal isolates on the spinach cultivar 'Viroflay', and DNA sequence analysis of the isolates, the symptoms on spinach leaves for two sets of samples were caused by Colletotrichum coccodes and Colletotrichum truncatum, and leaf spots resembling damage from windblown sand were caused by Myrothecium verrucaria. This is the first report of spinach leaf spot diseases caused by C. coccodes, C. truncatum, and M. verrucaria in the United States. C. coccodes and C. truncatum caused severe symptoms on the spinach cultivar 'Viroflay', whereas M. verrucaria caused symptoms of intermediate severity. Fungicide efficacy tests demonstrated that chlorothalonil, mancozeb, pyraclostrobin, fluxapyroxad + pyraclostrobin, and penthiopyrad were completely effective at preventing leaf spots caused by any of these pathogens when applied 24 h before inoculation of 'Viroflay' plants in greenhouse trials